La Turquie et l’Union européenne - Guy Baudelle; Benoit Montabone (EchoGéo)
This article investigates the various possible evolutions of the relations between Turkey and the European Union on the horizon 2020. Four resulting geopolitical scenarios are introduced: European anchoring (the normative scenario), Integration at risk (the trend line scenario), Diversification of partners (the alternate scenario), and at last Strategic overthrow (the nightmare one). In every case, the access to the hydrocarbons of Caucasus and Caspian Sea plays a key role.